Advances in Palladium‐Catalyzed Cascade Cyclizations. Issue 20 (9th October 2018) - Biemolt, Jasper; Ruijter, Eelco
Abstract: The past decades in organic chemistry have witnessed significant improvements in synthetic efficiency as a result of considerable progress in cascade reactions, tandem reactions, and related one‐pot processes. These methods are less time‐consuming and produce less waste compared to the classical stepwise approach. However, cascade chemistry requires a more careful design and compatible reaction types for success. Palladium‐catalyzed cross‐coupling reactions, with their well understood multistep catalytic cycles, form a promising basis for the design of cascade reactions. Furthermore, they are compatible with a range of functional groups and can be combined with a range of secondary transformations. The resulting palladium‐catalyzed cascade reactions have provided access to a plethora of complex small molecules of high medicinal relevance. This review provides an overview of the developments in palladium‐catalyzed cascade reactions since 2011, classified according to the initiation, propagation, and termination steps comprising the palladium cascade reactions. This classification should assist the reader and may provide inspiration for the design of new cascade reactions. Abstract :